2002
DOI: 10.1046/j.1365-2958.2002.02905.x
|View full text |Cite
|
Sign up to set email alerts
|

Competitive interaction of the OxyR DNA‐binding protein and the Dam methylase at the antigen 43 gene regulatory region in Escherichia coli

Abstract: SummaryThe antigen 43 surface protein of Escherichia coli is expressed in a phase-variable manner by a mechanism involving alternative activation and repression of transcription of the agn43 gene. The repressor is the OxyR DNA-binding protein, and its binding site was found to be located downstream of the agn43 transcription start site in a region of DNA that encompasses three 5¢-GATC-3¢ sequences that are subject to Dam-mediated DNA methylation. It has been suggested previously that the phase-variable express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
67
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 58 publications
4
67
0
1
Order By: Relevance
“…Cytosine methylation is a key regulator of gene expression in mammals, with major influence on processes such as development and cancer progression. In bacteria, however, DNA adenine methylation has been recognized as a regulator of gene expression, primarily by influencing the activities of transcription factors whose effects are correlated with the target's methylation status 14,15 . However, until very recently 27 when cytosine methylation was shown to regulate ribosomal gene expression in stationary phase, no role for cytosine methylation in gene expression control had been documented for bacteria, at least for enterobacteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytosine methylation is a key regulator of gene expression in mammals, with major influence on processes such as development and cancer progression. In bacteria, however, DNA adenine methylation has been recognized as a regulator of gene expression, primarily by influencing the activities of transcription factors whose effects are correlated with the target's methylation status 14,15 . However, until very recently 27 when cytosine methylation was shown to regulate ribosomal gene expression in stationary phase, no role for cytosine methylation in gene expression control had been documented for bacteria, at least for enterobacteria.…”
Section: Resultsmentioning
confidence: 99%
“…The beststudied solitary methyltransferase in E. coli is DNA adenine methyltransferase, which targets the G m ATC motif 13 . This methyl mark has important roles in regulating on-off gene expression by influencing the binding properties of transcription factors to DNA sites containing the methylated motif 14,15 ; it also influences replication by regulating the recruitment of the initiator of replication to the origin of replication 16,17 and regulates DNA repair by informing the methyl-directed mismatch repair system about the age of the DNA strand [18][19][20] . Another well-studied adenine methyltransferase is CcrM in Caulobacter crescentus, which methylates the GANTC site and acts as a cell cycle regulator 21 .…”
mentioning
confidence: 99%
“…The a subunit, on the other hand, remains attached to the bacterial cell surface via interactions with the b subunit (Henderson et al, 2004). The expression of Ag43 is phase-variable with switching rates of~10 23 per cell per generation due to the concerted actions of Dam methylase (positive regulation) and OxyR (negative regulation) (Henderson & Owen, 1999;Schembri et al, 2003a;Waldron et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The a subunit, on the other hand, remains attached to the bacterial cell surface via interactions with the b subunit (Henderson et al, 2004). The expression of Ag43 is phase-variable with switching rates of~10 23 per cell per generation due to the concerted actions of Dam methylase (positive regulation) and OxyR (negative regulation) (Henderson & Owen, 1999;Schembri et al, 2003a;Waldron et al, 2002).Ag43 dramatically enhances biofilm formation (Danese et al, 2000;Kjaergaard et al, 2000b; Reisner et al, 2003) and is specifically correlated with the biofilm mode of growth (Schembri et al, 2003b). Recent work has demonstrated that Ag43 expression is correlated with biofilm formation by uropathogenic E. coli during infection of bladder cells (Anderson et al, 2003) and in enteropathogenic E. coli (Torres et al, 2002).…”
mentioning
confidence: 99%
“…The flu promoter region contains three GATC sites, which overlap a recognition sequence for OxyR (9,10,13). When the GATC sites are methylated, OxyR cannot bind; conversely, bound OxyR prevents methylation (29).…”
mentioning
confidence: 99%